2011
DOI: 10.1007/s00586-011-2133-7
|View full text |Cite
|
Sign up to set email alerts
|

Paget disease of the spine: an evaluation of 101 patients with a histomorphometric analysis of 29 cases

Abstract: Introduction Paget's disease of bone (PDB) is the second most frequent metabolic bone disease with the spine being a common site of manifestation. Still, neither the disease's etiology nor reasons for its manifestation at preferred skeletal sites are understood. The aim of the current study was therefore to perform a histologic and histomorphometric analysis of PBD biopsies of the spine to achieve a more detailed understanding concerning PDB activity and characteristics. Materials and methods Out of 754 cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…PD was first described in 1877 by Sir James Paget in 5 patients [7,8]. PD is a common disease whose prevalence increases with age from about 1% in adult Caucasians aged 40 to 50 years to 10-11% after 80 years of age [9][10][11][12].…”
Section: Epidemiology Of Paget's Disease (Pd)mentioning
confidence: 99%
“…PD was first described in 1877 by Sir James Paget in 5 patients [7,8]. PD is a common disease whose prevalence increases with age from about 1% in adult Caucasians aged 40 to 50 years to 10-11% after 80 years of age [9][10][11][12].…”
Section: Epidemiology Of Paget's Disease (Pd)mentioning
confidence: 99%
“…The pathological environment of bone diseases alters not only bone cell activity but also the morphology and concentration of osteoblastic and osteoclastic cells. In examining the limited histomorphometric studies, a range of precursor bone cell ratios for physiological and bone diseases was observed (Table ) . Table lists the number of osteoclasts and osteoblasts per millimeter of bone surface, following the standard of histomorphometry defined by the American Society for Bone and Mineral Research .…”
Section: Bone Pathologymentioning
confidence: 99%
“…Furthermore, histology shows morphology differences, as compared with normal cells, of osteoclasts and osteoblasts involved in Paget's disease. Advances in understanding the cellular etiology of common and rare bone diseases will reveal the morphological abnormalities and osteoclast to osteoblast ratios specific to the particular disease state …”
Section: Bone Pathologymentioning
confidence: 99%
See 2 more Smart Citations